E-Learning for Life - With A Difference - Ayob, Aminah; Mohamed, Abdul Rashid (2004)
This is a project jointly sponsored by the Malaysian Ministry of Education, United Nation Development Programme, and Coca-cola Far East Limited. The spesific objectives of the project were to: Equip some hub schools with physical and thecnical infrastructure and facilities: Provide training to the teachers and students to initiate the multiplier effect and; Improve the teaching and learning culture. However, the main objective of this paper is to discuss the mobilization of the local community to participate in this project.